Análise numérica de normas sobre o reforço estrutural com compósitos reforçados de fibra de carbono (CFRP) em vigas de concreto armado submetidas ao cisalhamento - Schultz, Jacqueline da Luz (2021)
The study of reinforced concrete structures is essential for understanding the useful life of the part, as well as a preventive maintenance program. There are several causes for the deterioration of the structure, leading to the need for restoration, reinforcement or limitation in the use of the construction. After the diagnosis of a pathological manifestation, the intervention to be applied is defined. Among the materials for structural reinforcement in concrete beams, there is the use of composite materials. Thus, it is necessary to study this material. Fiber-reinforced composites are formed by the matrix, which unites the macro-components and gives shape to the material and the fiber, whose main role is to resist most of the load applied to the system. The three most common types of fiber are glass, aramid and carbon, the latter being the focus of this study, comparing shear reinforcement in reinforced concrete beams using international standards, as there is no regulation for this material in Brazil. Therefore, theoretical and numerical studies on the subject were carried out, through the numerical analysis of three international standards. Different equations parameters of the ACI Committe 440.2R (2017), CEB-FIP Bulletin 14 (2001) and CNR-DT 200.R1 (2013) methods were analyzed. With the obtaining of strength data according to the variable under study, comparisons were made between the chosen methods, with different types of applications. When comparing the different models studied, the ACI 440.2R (2017) model is bolder, that is, higher values among the other models occur in the four parameters analyzed, while the CEB-FIP model: Bulletin 14 (2001) is the most conservative, that is, with lower values. In terms of considering the parameters of the models, the highlight is the CNR-DT 200.R1 (2013) model, which considers the bonding stress between the substrate and the reinforcement, while the other standards do not.